A Preclinical Investigation of Estrogenic Bone Protection in a Hypertensive Rat Model Under Gender-Affirming Hormone Therapy - Lucas Streckwall; Germán A. Colareda; Daiana Escudero; Romina G. Diaz; Juan M. Fernández (Biology)
The goal of gender-affirming hormone therapy (GAHT) is to align an individual’s physical characteristics with their gender identity by suppressing endogenous sex hormones and replacing them with those consistent with their gender. Transgender women undergoing GAHT are at higher risk of cardiovascular complications, and since clinical evidence suggests that hypertension is associated with increased bone loss, we investigated the effects of estrogen treatment on bone health in a hypertensive transgender animal model. Male spontaneously hypertensive rats were orchiectomized (Orch), and half of them received estrogen treatment (Orch + Es), while a third group remained intact as controls. Bone marrow progenitor cells (BMPCs) were isolated to assess osteogenic potential, and femurs were collected for histological and mechanical analysis. BMPCs from Orch + Es rats exhibited enhanced osteogenic potential compared to those from Orch rats. Histological analysis revealed a higher number of osteocytes and fewer adipocytes in the Orch + Es group. Mechanical testing showed reduced bone strength in Orch rats, which was partially preserved in Orch + Es animals. In conclusion, estrogen administration mitigated the deleterious effects of testosterone depletion on BMPCs and provided protective effects on bone structure and strength in this preclinical model of GAHT in hypertensive rats.